Soil liquefaction during recent large-scale earthquakes : selected papers from the New Zealand - Japan Workshop on Soil Liquefaction During Recent Large-Scale Earthquakes, Auckland, New Zealand, 2-3 December 2013 /: selected papers from the New Zealand - Japan Workshop on Soil Liquefaction During Recent Large-Scale Earthquakes, Auckland, New Zealand, 2-3 December 2013. ([2014]) - Unknown
No abstract available